PHITS-Based Simulation of Dose Distributions and Secondary Particle Fluence from Light and Heavy Ions at Therapeutic Energies in a Water Phantom - Dalumpines, C. G. M.; Peñonal, G. F. I.; Aringa, H. P.; Convicto, V. C. (Atom Indonesia, 2025)
Comprehensive dosimetric evaluation of light and heavy ions such as protons, alpha particles, carbon, and oxygen ions is essential for advancements in radiation therapy and space applications. This study employed the Particle and Heavy Ion Transport code System (PHITS) to simulate dose distributions and secondary particle fluence in a water phantom across a range of therapeutic ion energies. A 30 × 30 × 30 cm³ water phantom with 2.0 × 108 primary particles at a Source to Surface Distance (SSD) of 100 cm were irradiated using mono energetic axial source. This simulation study also evaluated particle fluence of secondary particles such as electrons, positrons, and neutrons. Results showed that positron fluence concentrates around the water phantom, dispersing more at higher energy, while neutron flux focuses along the source path. The PHITS generated Percent Depth Dose (PDD) curves illustrate varied dose deposition patterns for each ion at different energies. For the highest energy considered, the simulated Bragg peak positions deviated by not more than 4.55 % from the experimental data, with simulation uncertainties kept below 0.1 %, ensuring accurate dose analysis. Helium ions (alpha particles) exhibited favorable treatment characteristics such as lower entrance dose, minimal lateral scattering, and reduced fragmentation consistent with the experimental findings. Additionally, the spatial distributions of electrons, positrons, and neutrons show elevated concentrations near the water phantom, indicating potential benefits for enhancing treatment precision.